Salmonella Carriage in Peripheral Lymph Nodes and Feces of Cattle at Slaughter Is Affected by Cattle Type, Region, and Season - Wottlin, Lauren R.; Edrington, Tom S.; Anderson, Robin C. (Frontiers in Animal Science, 2022)
Salmonella is a significant food safety concern in commercial beef production, and some contamination is thought to occur by inclusion of Salmonella-infected peripheral lymph nodes (LN) in ground beef and through fecal contamination. Surveillance in processing plants assists packers in risk management of Salmonella by understanding seasonal trends and risks associated with different cattle types. Approximately 25 fecal samples and 20 LN were collected from animals representing each of 5 cattle types (cull beef cattle, cull dairy cows, conventional feedlot cattle, all-natural feedlot cattle raised without pharmaceuticals, and grass-finished cattle) and each of 5 climate regions (mixed-temperatures and dry, mixed-temperatures and humid, hot and humid, hot and dry, cold) during each of 3 seasons (summer, fall, winter) to better characterize Salmonella inputs into a commercial cattle processing facility. In total, 1,840 fecal samples and 1,550 LN samples were collected. Fecal samples and LN were cultured for Salmonella, and select isolates were serogrouped and screened for antimicrobial resistance. Conventional feedlot cattle had the highest LN Salmonella concentrations (1.17 log10 CFU/g LN) in this data set, while cull dairy cows had the highest fecal Salmonella concentrations (1.96 log10 CFU/g feces). Conventional feedlot cattle and cull dairy cows had the greatest Salmonella prevalence in both LN (32 and 18%, respectively) and feces (37 and 49%, respectively), while all-natural feedlot cattle had the lowest prevalence in the LN (3%) and feces (7%). As expected, Salmonella prevalence and concentration was lowest for all cattle types during winter compared to warmer seasons. When examined by climate region, a greater Salmonella prevalence in both feces and LN was observed in climate region 4 (hot-dry), than the other regions. Only 21 of 50 Salmonella isolates examined for antimicrobial susceptibility were identified as multidrug resistant (MDR); cull dairy cows were responsible for 48% of MDR isolates, cull beef cattle were responsible for 38%, and conventional feedlot, grass-fed, and all-natural feedlot cattle were each responsible for 4.8%. These results indicate that different production schemes, season, and climate region may influence which cattle are most likely to introduce Salmonella to the abattoir, allowing for greater risk awareness during the slaughter process.